Analysis of Prognostic Risk Factors Determining Poor Functional Recovery After Comprehensive Rehabilitation Including Motor-Imagery Brain-Computer Interface Training in Stroke Patients: A Prospective Study - Wu, Qiong; Ge, Yunxiang; Ma, Di; Pang, Xue; Cao, Yingyu; Zhang, Xiaofei; Pan, Yu; Zhang, Tong; Dou, Weibei (Frontiers in Neurology, 2021)
Objective: Upper limb (UL) motor function recovery, especially distal function is one of the main goals of stroke rehabilitation as it is important to perform activities of daily living. The efficacy of Motor-Imagery brain-computer interface (MI-BCI) has been demonstrated in stroke patients. However, most stroke patients receive comprehensive rehabilitation including MI-BCI and routine training. Risk factors for inadequate distal UL recovery in these patients remain unclear. The present study was intended to investigate the independent risk factors that might lead to inadequate distal UL recovery of stroke patients after comprehensive rehabilitation including MI-BCI (CRIMI-BCI). Methods: This prospective study recruited 82 patients with stroke who undertook CRIMI-BCI. MI-BCI training was performed 60 min per day, 5 days per week for 4 weeks. The primary outcome was improvement of wrist and hand part of Fugl-Meyer Assessment (δFMA-WH). The improvement was classified into efficient group (EG, δFMA-WH > 2) and inefficient group (IG, δFMA-WH ≤ 2). Clinical and demographic data were analyzed by binary logistic regression, including aphasia, spasticity of affected hand (assessed by Modified Ashworth Scale [MAS-H]), initial UL function, age, gender, time since stroke (TSS), lesion hemisphere and lesion location. Results: A total of 73 patients completed this study. After training, all patients showed significant improvement in FMA-UL, FMA-SE, and FMA-WH (p< 0.000, respectively). There were 35 cases (47.9%) in the IG group and 38 cases (52.1%) in the EG group. At multivariate analysis, presence of aphasia (odds ratio [OR] 4.617, 95% confidence interval [CI] 1.435 14.860; p<0.05), initial FMA-UL score≤30 (OR 5.158, 95% CI 1.150 23.132; p<0.05), and MAS-H ≥level I+ (OR 3.810, 95% CI 1.231 11.790; p<0.05) were risk factors for inadequate distal UL recovery in patients with stroke after CRIMI-BCI. Conclusion: We concluded that CRIMI-BCI improved UL function in stroke patients with differentiated effectivity. Inferior initial UL function, significant hand spasticity and presence of aphasia were identified as independent risk factors for inadequate distal UL functional recovery in stroke patients after CRIMI-BCI.